Embedding skills policy in economic development policy : reflections on the COVID-19 skills strategy adopted in South Africa - Allais, Stephanie [Verfasser] (My University, 2022)
"In South Africa, the COVID-19 pandemic induced ruptures aggravated the systemic problems of TVET and in particular that of work-based learning. National COVID-19 responses as outlined in the Economic Reconstruction and Recovery Plan (ERRP) provided an opportunity for shifting away from simple sup ply–demand dichotomies regarding skills. Rather than skills being instrumental to the demand of the economy, skills development is considered an integral and mutually beneficial part of economic devel opment. Thus, the COVID-19 skills strategy advocates skills policies, planning and provision as embed ded in economic development, to support economic growth and development interventions. The text highlights how the crisis-induced new approach may be transferred into mid-term strategic alignments and describes the core interventions." (Author's abstract ; BIBB-Doku)
Keywords: I 2.3.1 Afrika; G 1.2.3 Qualifikationsentwicklungen; 370; Berufsbildung; Berufsausbildung; Pandemie; Südafrika; Lernen am Arbeitsplatz; Qualifikationsentwicklung